Adsorbent comprising highly hydratable lithium-bound aluminum hydroxide composition

By controlling the pH effect to form and process a gel-like material, the problem of difficulty in preparing LIAH compositions and low lithium absorption capacity in the prior art is solved, a highly hydratable H2-LIAH composition is prepared, and efficient lithium recovery is achieved.

CN119343180APending Publication Date: 2025-01-21SUMMIT NANOTECH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380043938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult to effectively prepare lithium-bound aluminum hydroxide (LIAH) compositions with high hardness, high selectivity to lithium and high lithium absorption capacity in the prior art, and traditional processes have problems such as long preparation time and low lithium absorption capacity.

Method used

By controlling the pH effect to form a gel-like material and processing it through an appropriate curing scheme, a highly hydratable lithium-bound aluminum hydroxide (H2-LIAH) composition is prepared with a lattice structure that extensively binds crystalline hydrates.

Benefits of technology

The preparation of H2-LIAH composition with high lithium absorption capacity, hardness and physical durability is achieved, which is suitable for efficient recovery of lithium from brine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343180A_ABST
    Figure CN119343180A_ABST
Patent Text Reader

Abstract

The present disclosure relates to adsorbents for selective extraction of metals from solutions, and more particularly to highly hydratable lithium bound aluminum hydroxide (H2-LIAH) compositions for lithium extraction. The H2-LIAH compositions of the present disclosure differ from conventional LIAH compositions at least in part by their crystalline hydrate: lithium molar ratios, which can be easily detected by analytical characterization. H2-LIAH compositions of the present disclosure can be readily: (i) prepared by a manufacturing method as described herein; (ii) incorporation into an apparatus for recovering lithium from brine as described herein; and / or (iii) use in a process for recovering lithium from brine as described herein. The H2-LIAH compositions of the present disclosure are developed after the discovery of a surprising pH effect that unexpectedly forms a gelatinous material during manufacture. The gel-like material may be tailored to the H2-LIAH compositions having unconventional properties as described herein.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority under applicable law to U.S. Provisional Patent Application No. 63 / 339,170, filed on May 6, 2022, the entire contents of which are incorporated herein by reference for all purposes. Technical Field

[0003] The present disclosure relates generally to adsorbents for selectively extracting metals from solutions, and more particularly to lithium-bound aluminum hydroxide (LIAH) compositions for lithium extraction. Background Art

[0004] Lithium-incorporated-aluminum-hydroxide (LIAH) compositions are a promising class of inorganic adsorbents for direct lithium extraction (DLE). DLE is an alternative to traditional lithium recovery methods such as open-pit mining and Great Basin evaporation, both of which can result in land destruction, potential pollution, and / or high water consumption. DLE may mitigate these impacts because it utilizes selective adsorbents to extract lithium from brines.

[0005] LIAH compositions can be effective adsorbents for extracting lithium from various types of brines, and the preparation and / or application of these compositions often require fewer chemical inputs than alternative inorganic adsorbents. Unfortunately, however, conventional methods for preparing LIAH adsorbent compositions are limited by synthetic constraints, leaving little room for tailoring the final composition to desired properties (e.g., high hardness, high selectivity for lithium, high lithium uptake capacity, narrow particle size distribution, etc.). These characteristics may be central to the widespread application of DLE.

[0006] Gibbsite impregnation is a traditional method for preparing LIAH compositions. The process can be complicated by long preparation times (e.g., due to slow dissolution of gibbsite). In addition, adsorbents produced by gibbsite impregnation tend to have low lithium uptake capacities.

[0007] In situ precipitation of LIAH compositions has been explored as a method for making lithium adsorbents. However, reported processes tend to produce products with broad particle size distributions, low crystallinity, and / or low lithium uptake capacity.

[0008] Hydrothermal processes have also been explored to prepare LIAH compositions. Unfortunately, these processes produce adsorbents subject to a number of limitations and the processes themselves can result in unacceptable cost and / or complexity given the high pressure and / or high temperature parameters of these processes.

[0009] There is an unmet need for new LIAH compositions suitable for extracting lithium from brines. There is also an unmet need for: (i) methods of making new LIAH compositions that can be tailored for desired properties; (ii) apparatus for recovering lithium from brines using new LIAH compositions; and (iii) methods of recovering lithium from brines using new LIAH compositions. Summary of the invention

[0010] The present disclosure reports a method comprising a highly hydrated lithium-bonded aluminum hydroxide (H 2 After extensive research on alternative methods for preparing lithium adsorbents, which revealed a surprising pH effect during the manufacturing process, the H-adsorbent of the present disclosure was developed. 2 -LIAH compositions. As described in the present disclosure, pH effects can be exploited to unexpectedly form gel-like materials that can then be processed into LIAH compositions having desired properties. Analytical characterizations indicate that gel formation is exothermic and that the resulting material has a lattice structure that is extensively bound to crystalline hydrates. Without wishing to be bound by any particular theory, the H 2 -Crystalline hydrate association in LIAH compositions can affect interplanar spacing and / or lattice formation during crystallization, and this may explain why the gel-like material formed during the manufacturing process can be tailored for desired properties (e.g., higher lithium uptake capacity, higher hardness, higher physical durability under operating conditions, higher chemical durability under operating conditions, larger average particle size and / or narrower particle size distribution) by selecting and executing an appropriate curing regimen (e.g., aging, rinsing, drying, and sieving).

[0011] In the context of the present disclosure, the terms "crystalline hydrate" and "crystalline hydrates" are used interchangeably and refer to a substance that can detect an endothermic transition at about 270°C to about 350°C by differential scanning calorimetry (DSC). Therefore, one skilled in the art can easily determine whether crystalline hydrates are present in a material and / or the degree of association of crystalline hydrates. The present disclosure provides the following teachings: Based on DSC data, in combination with complementary characterizations (including inductively coupled plasma optical emission spectroscopy (ICP-OES), thermogravimetric analysis (TGA) and / or X-ray diffraction (XRD)), the molar ratio of crystalline hydrate to lithium is determined. The H of the present disclosure 2 -LIAH compositions differ from conventional LIAH compositions at least in part in their molar ratio of crystalline hydrate:lithium, as described in the appended claims. 2 -LIAH compositions can be readily: (i) prepared by the manufacturing methods described in the present disclosure; (iii) incorporated into an apparatus for recovering lithium from brine; and / or (iii) used in a method for recovering lithium from brine.

[0012] One aspect of the present disclosure relates to an adsorbent for recovering lithium from a lithium-containing solution, the adsorbent comprising H 2 - A LIAH composition having a molar ratio of crystalline hydrate:lithium of at least about 2.1:1.0.

[0013] In one embodiment of the present disclosure, the H 2 The LIAH composition has a molar ratio of crystalline hydrate:lithium of about 2.1:1.0 to about 4.3:1.0.

[0014] In one embodiment of the present disclosure, the H 2 The LIAH composition has a molar ratio of crystalline hydrate:lithium of about 2.1:1.0 to about 2.9:1.0.

[0015] In one embodiment of the present disclosure, the H 2 The LIAH composition has a molar ratio of crystalline hydrate:lithium of about 2.9:1.0 to about 4.0:1.0.

[0016] In one embodiment of the present disclosure, the H is determined according to DSC, ICP-OES, TGA or a combination thereof. 2 - The molar ratio of crystalline hydrate:lithium of the LIAH composition.

[0017] In one embodiment of the present disclosure, the H 2 The XRD pattern of the LIAH composition has 2θ reflection peaks at approximately 11.5° 2θ, 23.1° 2θ, 35.0° 2θ, 35.7° 2θ, or a combination thereof.

[0018] In one embodiment of the present disclosure, the H 2 The XRD pattern of the -LIAH composition does not have a 2θ reflection peak at 18.2° 2θ.

[0019] In one embodiment of the present disclosure, the H 2 - The LIAH composition has an aluminum:lithium molar ratio of at least about 1.9:1.0.

[0020] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a molar ratio of aluminum:lithium of about 2.0:1.0 to about 3.0:1.0.

[0021] In one embodiment of the present disclosure, the H 2 The LIAH composition has a molar ratio of aluminum:lithium of about 2.4:1.0 to about 2.6:1.0.

[0022] In one embodiment of the present disclosure, the H2 -LIAH composition is as described in Formula 1:

[0023] Li a X·mAl(OH)3·nH2O cr Formula 1

[0024] in:

[0025] a is about 1;

[0026] X is a monovalent anion;

[0027] m is from about 1.9 to about 3.0;

[0028] n is from about 2.4 to about 4.3; and

[0029] H2O cr Represents a crystalline hydrate.

[0030] In one embodiment of the present disclosure, the H 2 -LIAH composition is a lithium aluminum layered double hydroxide composition.

[0031] In one embodiment of the present disclosure, the adsorbent further comprises a binder, a coating agent or a combination thereof.

[0032] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a lithium uptake capacity of at least about 8.0 mg / mL.

[0033] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a lithium uptake capacity of at least about 9.0 mg / mL.

[0034] In one embodiment of the present disclosure, the H 2 - The lithium uptake capacity of the LIAH composition is from about 9.5 mg / mL to about 12.0 mg / mL.

[0035] In one embodiment of the present disclosure, the H 2 - The LIAH composition can be processed to provide a particle size distribution in which at least about 40% of the particles are between about 500 μm and about 1000 μm.

[0036] In one embodiment of the present disclosure, the H 2 - The LIAH composition can be processed to provide a particle size distribution in which at least about 50% of the particles are between about 500 μm and about 1000 μm.

[0037] In one embodiment of the present disclosure, the H 2- The LIAH composition can be processed to provide a particle size distribution in which at least about 55% of the particles are between about 500 μm and about 1000 μm.

[0038] In one embodiment of the present disclosure, by 2 The LIAH composition is suspended in deionized water to provide a solution having a pH of about 7.0 to about 6.2.

[0039] In one embodiment of the present disclosure, by 2 - The LIAH composition was suspended in deionized water to provide a turbidity value of less than 10 NTU.

[0040] In one embodiment of the present disclosure, by 2 - The LIAH composition was suspended in deionized water to provide a turbidity value of less than 5 NTU.

[0041] In one embodiment of the present disclosure, by 2 The LIAH composition is suspended in deionized water to provide a turbidity value of about 2.5 NTU to about 5 NTU.

[0042] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a Mohs hardness of at least about 5.0.

[0043] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a Mohs hardness of at least about 6.0.

[0044] In one embodiment of the present disclosure, the H 2 - The LIAH composition has a Mohs hardness of at least about 7.0.

[0045] In one embodiment of the present disclosure, the H 2 - The LIAH composition is robust to physical degradation for at least about 500 column cycles.

[0046] In one embodiment of the present disclosure, the H 2 - The LIAH composition is robust to physical degradation for at least about 5000 column cycles.

[0047] One aspect of the present disclosure relates to a method for manufacturing H 2 - A method for a LIAH composition, the method comprising:

[0048] (i) contacting an initial aliquot of a hydroxide solution with an initial aliquot of a solution comprising a lithium halide and an aluminum halide to form a reaction mixture, wherein the hydroxide solution is in excess and the pH of the reaction mixture is at least about 9.0;

[0049] (ii) adding an additional aliquot of a solution comprising a lithium halide and an aluminum halide to the reaction mixture and lowering the pH of the reaction mixture to less than about 4.0;

[0050] (iii) allowing the reaction mixture to form a gel-like material; and

[0051] (iv) adding an additional aliquot of the hydroxide solution to the reaction mixture to raise the pH of the reaction mixture to about 6.0 to about 7.5.

[0052] In one embodiment of the present disclosure, in step (i), an initial aliquot of the hydroxide solution is added to an initial aliquot of the solution comprising lithium halide and aluminum halide.

[0053] In one embodiment of the present disclosure, in step (i), the pH of the reaction mixture is about 9.0 to about 11.0.

[0054] In one embodiment of the present disclosure, in step (i), the pH of the reaction mixture is about 10.0.

[0055] In one embodiment of the present disclosure, in step (ii), the pH of the reaction mixture is about 2.5 to about 4.0.

[0056] In one embodiment of the present disclosure, in step (ii), the pH of the reaction mixture is about 3.0.

[0057] In one embodiment of the present disclosure, in step (i), an initial aliquot of the solution comprising lithium halide and aluminum halide is added to an initial aliquot of the hydroxide solution.

[0058] In one embodiment of the present disclosure, the initial aliquot of the solution comprising lithium halide and aluminum halide and the further aliquots of the solution comprising lithium halide and aluminum halide are derived from the same stock solution.

[0059] In one embodiment of the present disclosure, the initial aliquot of the hydroxide solution and the additional aliquots of the hydroxide solution are derived from the same stock solution.

[0060] In one embodiment of the present disclosure, the solution comprising lithium halide and aluminum halide has a lithium:aluminum molar ratio of about 1.0:2.0 to about 1.0:3.0.

[0061] In one embodiment of the present disclosure, the concentration of the hydroxide solution is about 6.5M to about 8.0M.

[0062] In one embodiment of the present disclosure, the lithium halide is lithium fluoride, lithium chloride, lithium bromide, lithium iodide or a combination thereof.

[0063] In one embodiment of the present disclosure, the lithium halide is lithium chloride.

[0064] In one embodiment of the present disclosure, the aluminum halide is aluminum trifluoride, aluminum trichloride, aluminum tribromide, aluminum triiodide or a combination thereof.

[0065] In one embodiment of the present disclosure, the aluminum halide is aluminum trichloride.

[0066] In one embodiment of the present disclosure, the hydroxide solution is a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, a magnesium hydroxide solution or a combination thereof.

[0067] In one embodiment of the present disclosure, the hydroxide solution is a sodium hydroxide solution.

[0068] In one embodiment of the present disclosure, the addition rate of the hydroxide solution in step (i) and / or step (iv) is about 9.5 mL / min to about 10.5 mL / min.

[0069] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the reaction mixture is stirred to adjust the viscosity of the gel-like material.

[0070] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the temperature of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

[0071] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the pressure of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

[0072] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the reaction time is controlled to adjust the viscosity of the gel-like material.

[0073] In one embodiment of the present disclosure, in step (ii), step (iv) or a combination thereof, the rate of addition is controlled to adjust the viscosity of the gel-like material.

[0074] In one embodiment of the present disclosure, the method further comprises: (v) solidifying the gel-like material into H 2 -LIAH composition.

[0075] In one embodiment of the present disclosure, step (v) comprises drying at a temperature of about 85°C to about 105°C.

[0076] In one embodiment of the present disclosure, step (v) comprises drying for about 24 hours to about 75 hours.

[0077] In one embodiment of the present disclosure, step (v) comprises drying at a pressure of about 76 mmHg to 760 mmHg.

[0078] In one embodiment of the present disclosure, step (v) comprises aging, rinsing, drying, sieving or a combination thereof.

[0079] One aspect of the present disclosure relates to a sorbent produced by the method defined herein.

[0080] One aspect of the present disclosure relates to an apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising:

[0081] a container having an inlet, an outlet, and a continuous flow path therebetween; and

[0082] An adsorbent in the container, the adsorbent comprising H 2 - A LIAH composition having a molar ratio of crystalline hydrate:lithium of about 2.1:1.0 to about 4.3:1.0.

[0083] One aspect of the present disclosure relates to an apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising:

[0084] a container having an inlet, an outlet, and a flow path therebetween; and

[0085] an adsorbent in said container, wherein said adsorbent is as defined herein.

[0086] One aspect of the present disclosure relates to a method for recovering lithium from a lithium-containing solution, the method comprising:

[0087] contacting the lithium-containing solution with an adsorbent composition to extract lithium from the lithium-containing solution; and

[0088] eluting lithium from the adsorbent composition to form a lithium wash solution,

[0089] wherein the adsorbent composition comprises H 2 - A LIAH composition having a molar ratio of crystalline hydrate:lithium of about 2.1:1.0 to about 4.3:1.0.

[0090] One aspect of the present disclosure relates to a method for recovering lithium from a lithium-containing solution, the method comprising:

[0091] contacting the lithium-containing solution with an adsorbent composition to extract lithium from the lithium-containing solution; and

[0092] eluting lithium from the adsorbent composition to form a lithium wash solution,

[0093] wherein the adsorbent composition comprises H as defined herein 2 -LIAH composition.

[0094] A method for recovering lithium from a lithium-containing solution, the method comprising:

[0095] The lithium-containing solution is mixed with a mixture comprising H as defined herein 2 - contacting an adsorbent of a LIAH composition to extract lithium from the lithium-bearing solution; and

[0096] Lithium is eluted from the adsorbent to form a lithium elution solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] In the drawings and descriptions provided herein, like reference numerals denote like parts. For simplicity and clarity, not all drawings contain references to all parts and features, and references to some parts and features may appear in only one drawing. Parts and features of the present disclosure shown in other drawings can be easily inferred therefrom.

[0098] Figure 1 A differential scanning calorimetry (DSC) graph 100 is shown, which depicts the thermal conductivity of a conventional lithium aluminum hydroxide (LIAH) composition and a highly hydrated lithium-bound aluminum hydroxide (H 2 -LIAH) composition as a function of temperature.

[0099] Figure 2 A normalized thermogravimetric analysis (TGA) graph 200 is shown, which depicts the change in sample weight as a function of temperature (expressed as a relative percentage). 2 -LIAH compositions, and their main decomposition events are indicated.

[0100] Figure 3 An X-ray diffraction (XRD) pattern 300 is shown, which depicts two H 2 - characteristic crystal pattern of the LIAH composition, which overlaps with the characteristic crystal pattern of the traditional LIAH composition prepared by the gibbsite impregnation method. 2 -The main characteristic peaks of LIAH composition and traditional LIAH composition.

[0101] Figure 4 The H of the present disclosure is shown before high temperature drying 401 and after high temperature drying 402. 2Fourier transform infrared (FTIR) spectra of the LIAH composition are overlaid 400. The major aluminum-oxygen bonding absorbance bands are indicated.

[0102] Figure 5 The H of the present disclosure is shown 2 - Microscopic images of LIAH compositions and a standard decimal scale for referencing particle sizes (ie, each graduation represents 1 mm).

[0103] Figure 6 An absorption curve 600 is shown, which depicts the absorption of brine and H 2 - Changes in relative lithium concentration over time of LIAH adsorbent materials during lithium extraction cycles.

[0104] Figure 7 The H of the present disclosure is shown 2 - Lithium concentration versus time profile of the LIAH adsorbent material during multiple lithium extraction cycles.

[0105] Figure 8 An apparatus 800 for recovering lithium from a lithium-containing solution according to one embodiment of the present disclosure is shown. Figure 8 Also shown is a method 850 for recovering lithium from a lithium-containing solution according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0106] The following detailed description and examples are illustrative only and should not be construed as further limiting the scope of the present disclosure. On the contrary, the present disclosure is intended to cover all alternatives, modifications and equivalents that may be included as described in this specification. By reading the following non-limiting description and referring to the accompanying drawings, the purposes, advantages and other features of the compositions, methods and apparatus will become more apparent and will be better understood by those skilled in the art.

[0107] Most conventional methods for preparing LIAH compositions by in situ precipitation use Al(OH)3 rather than AlCl3 as a starting material because the latter is hazardous and can be difficult to handle safely. Conventional methods using AlCl3 as a starting material tend to employ a single addition step in which: (i) the LiCl / AlCl3 solution is slowly and controlled added to an alkaline (e.g., hydroxide) solution to reduce the pH to 6.5 to 7.0, but not significantly below that range; or (ii) the pH is not controlled during the addition of a stoichiometric amount of the LiCl / AlCl3 solution to the alkaline (e.g., hydroxide) solution, such that the final pH of the mixture is typically greater than 7, most likely 8.5 to 10.

[0108] In contrast, the manufacturing method of the present disclosure utilizes a pH reversal scheme that includes multiple steps. The pH reversal scheme of the present disclosure differs from the conventional method in that the amount and order of addition are controlled and / or selected so that the pH of the reaction mixture rapidly passes through the above range and drops to a minimum acidic value (e.g., about 3.0) before slowly returning to about 6.5 to about 7.0. In other words, the pH reversal scheme of the present disclosure rapidly passes through neutrality and then approaches neutrality from the acidic side of the pH scale. The pH reversal scheme of the present disclosure induces the formation of a gel-like material at or near the minimum pH. The formation of the gel can be easily detected based on the change in solution viscosity, and it has been determined that the mixing rate, reagent concentration, order of reagent addition (and / or other reaction parameters) can be changed to adjust the strength of the gel. The pH reversal scheme of the present disclosure 2 The properties of the LIAH compositions may be related to: (i) the strength of the gel produced in this manner; and (ii) the strength of the H-containing gel used to produce the final form. 2 -Specific curing protocols for LIAH compositions. Those skilled in the art with the benefit of the teachings of the present disclosure will recognize that controlling and optimizing batch scale-up parameters may affect the strength of the gel (e.g., mixing volume relative to reaction type, sizing of mixing equipment, and balance of reaction dilution relative to drying time constraints), and that specific curing protocols (e.g., proper homogenization and mixing during aging, rinsing to remove salt impurities, drying to remove moisture, and / or sieving to select particle size) may be employed to produce H tailored for one or more desired qualities. 2 - A LIAH composition as described herein.

[0109] As described above, analytical characterization shows that the H 2 -LIAH compositions have a lattice structure that is extensively bound to crystalline hydrates. In the context of the present disclosure, the terms "crystalline hydrate" and "multiple crystalline hydrates" are used interchangeably and refer to a substance for which an endothermic transition is detectable at about 270°C to about 350°C by differential scanning calorimetry (DSC). The crystalline hydrate may include water bound to or released from the crystalline lattice, partial decomposition products of the crystalline lattice, and / or complete decomposition products of the crystalline lattice. In the context of the present disclosure, crystalline hydrates are distinguished from "surface hydrates" because the term refers to a substance for which an endothermic transition is detectable at about 30°C to about 130°C by DSC.

[0110] Without wishing to be bound by any particular theory, the crystalline hydrate association in the LIAH compositions of the present disclosure may affect the interplanar spacing and / or lattice formation during the crystallization process. This process may explain why the gel-like material formed during the manufacturing process can be tailored for desired properties (e.g., higher lithium uptake capacity, higher lithium selectivity, higher hardness, higher physical durability under operating conditions, higher chemical durability under operating conditions, larger average particle size, and / or narrower particle size distribution) by selecting and executing an appropriate curing regimen (e.g., aging, rinsing, drying, and screening).

[0111] In view of the following description of the present disclosure in conjunction with the accompanying drawings without limiting the scope of the appended claims, 2 These and other teachings, objects, features, examples, scopes, thresholds and advantages of the present disclosure will be apparent to those skilled in the art from the description of specific embodiments of the present invention -LIAH compositions, including incorporation of these compositions into adsorbents for recovering lithium from brines, methods of making these compositions, incorporation of these compositions into apparatus for recovering lithium from brines, and use of these compositions in methods for recovering lithium from brines.

[0112] Contains H 2 - Adsorbents for LIAH compositions

[0113] A set of analytical techniques was used to analyze the H 2 -LIAH compositions were analyzed to confirm various properties as described below. Specific results are discussed in conjunction with typical examples and teachings to enable one skilled in the art to determine, for example, the crystalline hydrate: lithium ratio of the LIAH composition, and more generally to detect the H 2 -LIAH compositions are distinguished from conventional LIAH compositions. 2 -Analysis of LIAH compositions is not necessarily limited to the analytical techniques discussed below, and those skilled in the art will recognize that other characterization techniques may supplement, support, or replace one or more of the above analytical techniques without departing from the scope of the present disclosure.

[0114] H can be determined by DSC 2 - Endothermic transition of LIAH composition. One skilled in the art will understand the details of conventional DSC characterization employed in this disclosure. Figure 1 A DSC graph 100 is shown which depicts the relationship between a conventional LIAH composition 111 and the H 2 - Relative enthalpy of LIAH composition 121 as a function of temperature. 2The characteristic enthalpy event 122 of the LIAH composition has a unique characteristic onset temperature (about 270°C); in contrast, the conventional LIAH composition 112 is observed to have an onset temperature of about 200°C. Figure 1 Surface hydrate loss can be represented by a broad low-intensity enthalpy event centered around 80 °C for both materials105.

[0115] H can be determined by TGA 2 - Decomposition pattern of LIAH compositions. One skilled in the art will understand the details of conventional TGA characterization employed in the context of the present disclosure. Figure 2 A normalized TGA graph 200 is shown, which depicts a series of H prepared by various manufacturing methods of the present disclosure. 2 Sample weight change of LIAH composition with temperature (expressed as relative percentage). In this series, it can be seen that the main decomposition event 211 starts at about 270°C and ends at about 310°C. Figure 1 This is consistent with the DSC characterization in Figure 2 Surface hydrate loss can also be detected, as shown by reference numeral 212. Figure 2 The series presented in support the H prepared by the various manufacturing methods disclosed in this disclosure. 2 - General reproducibility of thermal decomposition parameters of LIAH compositions.

[0116] H can be determined by XRD 2 - Crystal diffraction pattern of a LIAH composition. One skilled in the art will understand the details of conventional XRD characterization employed in the context of the present disclosure. Figure 3 An XRD diffraction pattern 300 is shown, which depicts two H 2 - Characteristic crystal patterns (311 and 321) of LIAH compositions, which overlap with the characteristic crystal pattern 331 of conventional LIAH compositions made by the gibbsite impregnation process. 2 The main characteristic peak of the LIAH composition is at about 11.5°2θ (312). 2 -The other characteristic peaks 313, 314 and 315 of the LIAH composition are at about 23.1°2θ, about 35.0°2θ and about 35.7°2θ, respectively. The main characteristic peak of the conventional LIAH composition is at about 18.2°2θ (332). This peak is not 2 -LIAH compositions are not significantly present. In one embodiment of the present disclosure, H 2 -LIAH compositions have substantially Figure 3 XRD patterns (311 and 321) are shown.

[0117] The manufacturing information described in this disclosure and the subsequent H 2 -LIAH characterization data were used to determine the molecular formula summarized by Formula 1. Based on the typical H 2 -LIAH composition embodiments, specifically, the use of lithium chloride indicates that the integer "a" is 1 and the monovalent anion "X" is chloride. Therefore, the partial molecular formula can be initially determined as: LiCl·mAl(OH)3·nH2O cr .

[0118] Typical H of the present disclosure 2 -LIAH composition, the H of the present disclosure can be determined by ICP-OES 2 Elemental composition data of -LIAH compositions. Those skilled in the art will appreciate the details of conventional ICP-OES characterization employed in the context of the present disclosure. Typical H 2 -Elemental composition data of LIAH compositions.

[0119] Table 1: H analyzed by ICP-OES 2 -LIAH elemental composition.

[0120]

[0121] For the typical H 2 -LIAH composition, the ratio of aluminum to lithium (normalizing the molar concentration of lithium to 1) was therefore determined to be 2.32: 1. After normalizing the ratio relative to lithium, the proportion of aluminum can be entered into Formula 1 as an integer "m", and the partial formula can be further described as: LiCl·2.32Al(OH)3·nH2O cr.

[0122] In the context of the present disclosure, the crystalline hydrate:lithium ratio of a LIAH composition can be determined as follows.

[0123] TGA data can be used to distinguish specific heating zones where surface hydrates and crystalline hydrates are lost, respectively, during the analysis of hydrates containing LIAH materials. Table 2 summarizes typical H 2 - TGA data of the LIAH composition at two specific time points, which describes the temperature range in which crystalline hydrates can be observed.

[0124] Table 2: H during heating 2 -LIAH relative mass readings

[0125]

[0126] In the context of the present disclosure, the relative TGA mass value can be used to determine the relative mass loss (expressed as a percentage) for a crystalline hydrate, as summarized in Formula 2:

[0127] Relative loss 结晶 =Relative mass 120℃ - Relative mass 350℃ Formula 2

[0128] in:

[0129] Relative quality 120℃ is the relative mass TGA measurement at 120°C; and

[0130] Relative quality 350℃ is the relative mass TGA measurement value at 350°C.

[0131] For the typical H 2 -LIAH composition and its TGA data in Table 2, the relative mass loss of the crystalline hydrate was determined to be 20.387%.

[0132] In the context of the present disclosure, the molar ratio of crystalline hydrate: lithium can be calculated from the TGA data and the ICP-OES data by mass balance using Formula 3. The ICP-OES data is first evaluated to provide a molar ratio of aluminum: lithium, which is then used in Formula 3. Alternatively, if desired, the mass values ​​obtained from these data can be used to determine a similar ratio. Based on the data in Table 1, the typical H ratio of the present disclosure is determined. 2 - The LIAH composition has an aluminum:lithium ratio of about 2.3:1.0.

[0133]

[0134] in:

[0135] R,l is the molar ratio of lithium, which is normalized to 1;

[0136] R,n is the molar ratio of aluminum hydroxide to lithium;

[0137] MW x is the molecular weight of the species in question;

[0138] MW LiCl =42.40 g / mol;

[0139] MW AlOH3 =78.00 g / mol;

[0140] MW H2O =18.02 g / mol; and

[0141] Relative loss 结晶is the relative mass loss percentage of the crystalline hydrate.

[0142] For the typical H disclosed in this disclosure 2 -LIAH composition and its TGA data, the relative mass loss of the crystalline hydrate was determined to be 2.5. Therefore, the typical H 2 -Specific molecular formula of LIAH composition (final integer "n" has been determined). Thus, Formula 1 is determined as:

[0143] LiCl·2.3Al(OH)3·2.5H2O cry

[0144] A set of analytical techniques was used to evaluate the H 2 -LIAH material composition to determine the effect of loss of crystalline hydrates. Representative experimental results are summarized below.

[0145] Figure 4 The H of the present disclosure is shown before high temperature drying 411 and after high temperature drying 421. 2 Fourier transform infrared (FTIR) spectra of the -LIAH composition are overlaid 400. For discussion purposes, individual FTIR bands are identified and assigned to their respective materials. For simplicity, the x-axis is truncated by a rest 405. It can be noted that the general -OH bond stretching vibration absorbance of the two materials, H before high temperature drying 2 -LIAH composite showed a strong relative absorbance of 415, while the H 2 -LIAH composition showed a reduced absorbance of 425. 2 -LIAH composition, with reference numerals 416, 417 identifying the absorbance bands indicating aluminum binding. 2 The -LIAH composition exhibits a significant loss of the Al-O stretching vibration band 426 and a reduced Al-OH bending vibration band 427. Without wishing to be bound by any particular theory, the observed changes in the Al-O-bonding bands indicate that crystallinity is significantly lost due to high temperature drying. The loss of crystallinity associated with high temperature drying can also be observed in the DSC data listed above. Figure 1 The endotherm 301 observed in has no signs of a subsequent recrystallization event, as observed in the peak shape and the graph trend, such as a symmetrical Gaussian shape and a steep slope without supercooling recrystallization events.

[0146] Determine the H of the present disclosure 2-LIAH compositions and conventional LIAH compositions. In each case, the dried samples were suspended in deionized water and the pH of the resulting solution was measured using a calibrated pH meter. The results are listed in Table 3. It was found that the H 2 - The LIAH compositions have lower hydroxide retention than conventional LIAH compositions, which can improve the performance of lithium recovery adsorbents (especially in applications involving brines with high concentrations of divalent ions that tend to precipitate in the presence of hydroxide ions).

[0147] Table 3: H 2 - Excess hydroxide retention of LIAH compositions and conventional LIAH compositions

[0148] Composition pH of the solution <![CDATA[H 2 -LIAH Composition]]> 6.28 Traditional LIAH composition 6.20

[0149] The H of the present disclosure was evaluated by turbidity measurement. 2 The structural and chemical robustness of the H-LIAH compositions and conventional LIAH compositions are listed in Table 4. 2 The turbidity results of the HIAH composition of the present disclosure and the conventional LIAH composition are shown in FIG. 2 -The structural and chemical robustness of the LIAH compositions are improved, which may be related to their improved chemical durability as adsorbents for recovering lithium from brines.

[0150] Table 4: From H 2 - Turbidity measurements of decanted solutions from LIAH compositions and conventional LIAH compositions.

[0151] Composition Turbidity of solution (NTU) Average turbidity (NTU) <![CDATA[H 2 -LIAH Composition]]> 2.24、2.47、2.37、2.51 2.40 Standard LIAH composition 933、876、915、873 899

[0152] The scratch test and Mohs hardness scale were used to determine the H 2 The hardness of the H-LIAH composition and the conventional LIAH composition is shown in Table 5. 2 -LIAH composition and the hardness results of the samples related to the conventional LIAH composition. The results show that the H 2 -The improved hardness of the LIAH compositions may be related to their improved physical durability as adsorbents for recovering lithium from brines.

[0153] Table 5: H 2 - Scratch test results of LIAH composition and conventional LIAH composition.

[0154] Composition Observations Approximate hardness <![CDATA[H 2 -LIAH Composition]]> Easily scratched by glass / steel 6 Standard LIAH composition Easily scratched by copper wire 3

[0155] Figure 5 The H of the present disclosure is shown2 - A microscopic image of a LIAH composition and a standard decimal scale for reference particle size (i.e., each graduation represents 1 mm). The LIAH composition can be processed to provide a particle size distribution in which at least: (i) about 40% of the particles are between about 500 μm and about 1000 μm; (ii) about 50% of the particles are between about 500 μm and about 1000 μm; or (iii) at least about 55% of the particles are between about 500 μm and about 1000 μm.

[0156] The H of the present disclosure was determined using a laboratory scale column apparatus. 2 - Lithium absorption capacity of LIAH compositions and conventional LIAH compositions.

[0157] The apparatus has a laboratory stand and a jacketed glass column with an inner diameter of about 3.2 cm and a height of about 20 cm and a sieve plate to minimize particle loss. The column is heated by an external circulating water bath with a set operating temperature. In each case, a pre-weighed mass of the test composition (about 50 g to about 70 g) within a predetermined particle size range is transferred to the column. After pumping water or eluent (200 ppm lithium solution) through the column using the operating flow path (top to bottom), the filled adsorbent height is determined. In order to prepare the test composition for adsorption, an initial elution to a total of 10 bed volumes is performed using the eluent to remove entrained lithium. Subsequently, the adsorption and elution stages are performed at elevated temperatures of 40°C to 80°C using the prepared synthetic feed brine and the eluent, respectively. The synthetic brine includes the species listed in Table 6 (the concentrations of which are determined by ICP-OES or inductively coupled plasma mass spectrometry (ICP-MS)).

[0158] Table 6: Evaluation of H according to the present disclosure 2 - Composition of brine feed to LIAH composition

[0159] ion concentration lithium 600ppm to 800ppm sodium 96000ppm to 100000ppm Potassium 20000ppm to 25000ppm calcium 400ppm to 500ppm magnesium 4000ppm to 5000ppm boron 500ppm

[0160] The treatment volume of the adsorption stage was calculated using a target maximum lithium uptake capacity of 10 mg / g (based on the amount of adsorbent weighed and packed into the column - this correlates to 5 to 10 bed volumes). The flow rate was adjusted so that the flow rate of the fluid through the adsorbent was between 300 L / m2 / hour and 400 L / m2 / hour. To determine the performance of the test composition during the adsorption stage, samples were taken from the outlet (at the bottom of the column) at regular time intervals and the composition of each sample was determined by ICP-OES.

[0161] Figure 6 Graph 600, which depicts lithium concentration as a function of sampling time, provides a visual depiction of the capacity of the tested composition. Figure 6In the graph, the lithium concentration of the bulk solution is indicated by reference numeral 611, while the lithium concentration at the outlet is indicated by reference numeral 621. This can be described as a sharp drop in the lithium concentration at the outlet relative to the initial brine concentration. The lower lithium concentration persists for a period of time before starting to rise again (which is characteristic of the adsorbent), thus presenting a "bathtub" pattern. As the adsorbent approaches saturation, the outlet lithium concentration rises until it reaches the initial lithium concentration of the feed brine.

[0162] The more formal capacity measurement result was determined by the lithium adsorption amount calculated by equation 4.

[0163] Lithium absorbed = ([Li] 初始 -[Li] 最终 )×Vol 卤水 Formula 4

[0164] in:

[0165] Lithium absorbed = Total lithium absorbed (unit: mg)

[0166] [Li] 初始 : Initial lithium concentration (unit: mg / L)

[0167] [Li] 最终 : Final lithium concentration (unit: mg / L)

[0168] Vol 卤水 : The volume of brine tested (unit: L)

[0169] Then, the capacity of the adsorbent was calculated by Equation 5:

[0170]

[0171] As an example of continuous use, Figure 7 The H of the present disclosure used in one embodiment of the apparatus for recovering lithium from a lithium-containing solution according to the present disclosure and in the method for recovering lithium from a lithium-containing solution according to the present disclosure are shown. 2 An excerpt of process monitoring data 700 for a LIAH composition. For brevity, the x-axis is truncated by a rest 705. A typical cycle 711 first shows the loading of brine into the system and then the adsorption of lithium onto a H-loaded 2 - Changes in lithium concentration over the course of the LIAH column. The column performance is maintained over successive cycles so that chemical and / or physical durability can be assessed. Samples are taken from the outlet (at the bottom of the column) at regular time intervals and the composition of each sample is determined by ICP-OES.

[0172] In this embodiment, elution was performed using a volume of eluent equivalent to the feed brine at a flow rate corresponding to 300 L / m2 / hour to 800 L / m2 / hour. Sampling was performed (similar to the sampling during the adsorption stage). For adsorbent evaluation, two to three adsorption / elution cycles were performed using synthetic feeds before comparative evaluation using real brine samples.

[0173] One aspect of the present disclosure relates to an adsorbent for recovering lithium from a lithium-containing solution, the adsorbent comprising a LIAH composition having a molar ratio of crystalline hydrate: lithium of at least about 2.1:1.0. In the context of the present disclosure, the LIAH composition may include a single compound or a plurality of compounds. In one embodiment of the present disclosure, the molar ratio of crystalline hydrate: lithium of the LIAH composition may be from about 2.1:1.0 to about 4.3:1.0. In one embodiment of the present disclosure, the molar ratio of crystalline hydrate: lithium of the LIAH composition may be lower than about 2.4:1.0 to about 2.9:1.0. In one embodiment of the present disclosure, the molar ratio of crystalline hydrate: lithium of the LIAH composition may be lower than about 4.3:1.0. In one embodiment of the present disclosure, the molar ratio of crystalline hydrate: lithium of the LIAH composition may be lower than about 2.9:1.0 to about 4.0:1.0. Those skilled in the art who have the benefit of the teachings of the present disclosure should understand how to adjust the manufacturing conditions to provide a LIAH composition within the range. For example, the following parameters can be controlled to induce a higher crystalline hydrate:lithium molar ratio (reference numbers are associated with the method of manufacturing steps described herein):

[0174] - increasing the concentration of the hydroxide solution used in step (i) and / or step (iv);

[0175] - in step (i), raising the pH of the reaction mixture to above about 9.0 (e.g., to about 10.0 or about 11.0);

[0176] - in step (ii), lowering the pH of the reaction mixture to below about 4.0 (e.g., to about 3.0 or about 2.0);

[0177] - in step (iii), minimising high shear mixing; and / or

[0178] - reducing the reaction time of step (iii) and / or step (iv).

[0179] In one embodiment of the present disclosure, the molar ratio of crystalline hydrate: lithium of the LIAH composition can be determined by DSC, ICP-OES, TGA, or a combination thereof. 2-Analysis of LIAH compositions need not be limited to these analytical techniques. It will be appreciated by those skilled in the art that other characterization techniques may supplement, support or replace one or more of the above analytical techniques without departing from the scope of the present disclosure. In the context of the present disclosure, analysis by DSC may require that the sample be loaded into an aluminum transfer crucible prior to analysis. Each crucible may be covered, and each cover may be perforated with a sharp tip to allow gas to escape throughout the experiment. During the analysis, the sample may be treated from ambient temperature to 450°C at a constant heating rate. Experimental data on enthalpy changes during heating may be provided. In the context of the present disclosure, samples for TGA may be loaded into an aluminum transfer crucible. During the analysis, the sample may be treated from ambient temperature to 450°C at a constant heating rate. Experimental data on relative mass loss (%) during heating may be provided. In the context of the present disclosure, the sample may be digested with acid in a plastic vessel and diluted with deionized water for analysis before elemental analysis by ICP-OES (or alternatively, ICP-MS). In the context of the present disclosure, FTIR samples can be prepared by grinding the materials into powders, which can then be placed on an FTIR spectrometer equipped with an ATR accessory. Spectra can be acquired in the range of 4000–400 cm-1. In the context of the present disclosure, samples to be analyzed by XRD can be crushed and placed on an X-ray transparent support (e.g., single crystal silicon), and the samples are analyzed using Bragg-Brentano instrument geometry. In one embodiment of the present disclosure, the LIAH composition can be characterized by XRD as having 2θ reflection peaks at approximately 11.5°2θ, 23.1°2θ, 35.0°2θ, 35.7°2θ, or a combination thereof. Similarly, the LIAH composition of the present disclosure can be characterized by XRD as having no 2θ reflection peak at 18.2°2θ.

[0180] In one embodiment of the present disclosure, the molar ratio of aluminum:lithium of the LIAH composition may be at least about 1.9:1.0. In one embodiment of the present disclosure, the molar ratio of aluminum:lithium of the LIAH composition may be about 2.0:1.0 to about 3.0:1.0. In one embodiment of the present disclosure, the molar ratio of aluminum:lithium of the LIAH composition is about 2.4:1.0 to about 2.6:1.0. It will be appreciated by those skilled in the art that these elemental ratios may be determined by ICP or another suitable analytical technique.

[0181] In one embodiment of the present disclosure, the LIAH composition may be as described in Formula 1:

[0182] Li a X·mAl(OH)3·nH2O crFormula 1

[0183] in:

[0184] a is about 1;

[0185] x is a monovalent anion (e.g., F - , Cl - Br - and / or - );

[0186] m is from about 1.9 to about 3.0;

[0187] n is from about 2.4 to about 4.3; and

[0188] H2O cr Represents a crystalline hydrate.

[0189] In one embodiment of the present disclosure, the LIAH composition may be a lithium aluminum layered double hydroxide composition.

[0190] In one embodiment of the present disclosure, the adsorbent may further include a binder, a coating agent, or a combination thereof. Suitable agents may be organic agents or inorganic agents, and may include alginate, biochar, biopolymers, carbonaceous ores, clays, polyvinyl alcohol, methyl acrylate, graphene, metal organic frameworks, nanotubes, polyphenols, synthetic polymers, polysaccharides, silicates, and combinations thereof.

[0191] In one embodiment of the present disclosure, the lithium absorption capacity of the LIAH composition may be at least about 8.0 mg / mL. In one embodiment of the present disclosure, the lithium absorption capacity of the LIAH composition may be at least about 9.0 mg / mL. In one embodiment of the present disclosure, the lithium absorption capacity of the LIAH composition may be about 9.5 mg / mL to about 12.0 mg / mL. In one embodiment of the present disclosure, the LIAH composition may be processable to provide a particle size distribution with at least about 40% of the particles being about 500 μm to about 1000 μm. In one embodiment of the present disclosure, the LIAH composition may be processable to provide a particle size distribution with at least about 50% of the particles being about 500 μm to about 1000 μm. In one embodiment of the present disclosure, the LIAH composition may be processable to provide a particle size distribution with at least about 55% of the particles being about 500 μm to about 1000 μm. Those skilled in the art who have the benefit of the teachings of the present disclosure should understand how to adjust the manufacturing conditions to provide a LIAH composition within the range. For example, the following parameters can be controlled to induce larger particle sizes (reference numbers relate to the method of manufacturing steps described herein):

[0192] - increasing the concentration of the hydroxide solution used in step (i) and / or step (iv);

[0193] - in step (i), raising the pH of the reaction mixture to above about 9.0 (e.g., to about 10.0 or about 11.0);

[0194] - in step (ii), lowering the pH of the reaction mixture to below about 4.0 (e.g., to about 3.0 or about 2.0);

[0195] - in step (iii), minimizing high shear mixing;

[0196] - reducing the reaction time of step (iii) and / or step (iv);

[0197] - in step (v), drying the gel-like material at a temperature of about 85°C to 120°C;

[0198] - in step (v), drying the gel-like material to a thickness of at least about 4 cm;

[0199] - in step (v), drying the gelatinous material for about 24 hours to about 72 hours;

[0200] and / or

[0201] - In step (v), the gel-like material is dried to a mass reduction of about 30% to about 60%.

[0202] In one embodiment of the present disclosure, by suspending the LIAH composition in deionized water, a solution with a pH of about 7.0 to about 6.2 can be provided. 2 The concentration of residual hydroxide ions retained by the LIAH composition can be relatively low. 2 The LIAH composition is suspended in deionized water and can provide a solution having a pH of less than about 5, less than about 6, or about 6.5 to about 7. This may be beneficial because the formation of insoluble hydroxides may result from exposure to complex brines. Without wishing to be bound by any particular theory, complex brines may contain relatively high concentrations of divalent ions (such as Ca 2+ and Mg 2+ ), these divalent ions can precipitate out of solutions containing relatively high concentrations of hydroxide, and this can increase the pressure drop within the adsorbent column, leading to lower operating flow rates and lower lithium absorption performance. 2 -LIAH compositions can alleviate this problem.

[0203] In one embodiment of the present disclosure, by suspending the LIAH composition in deionized water, a turbidity value of less than 10NTU can be provided. In one embodiment of the present disclosure, by suspending the LIAH composition in deionized water, a turbidity value of less than 5NTU can be provided. In one embodiment of the present disclosure, by suspending the LIAH composition in deionized water, a turbidity value of about 2.5NTU to about 5NTU can be provided. This may be beneficial for DLE adsorbent process engineering as it may be associated with improved structural integrity in the process flow. In the context of the present disclosure, turbidity measurements may include: suspending a unit of material in deionized water and gently mixing to achieve dispersion. The suspension may be decanted into a separate beaker and the decanted solution may be subjected to turbidity measurements.

[0204] In one embodiment of the present disclosure, the LIAH composition may have a Mohs hardness of at least about 5.0. In one embodiment of the present disclosure, the LIAH composition may have a Mohs hardness of at least about 6.0. In one embodiment of the present disclosure, the LIAH composition may have a Mohs hardness of at least about 7.0. The hardness of the LIAH composition of the present disclosure may be characterized by the Mohs mineral hardness scale, which is a qualitative ordinal scale from 1 to 10 that characterizes the scratch resistance of various minerals by the ability of harder materials to scratch softer materials. In the context of the present disclosure, the determination of sample hardness (before manual grinding and sieving) may include: scratching with a harder object (e.g., a fingernail, a copper wire, a piece of glass, and a stainless steel pick), and noting whether the particles break or produce a lot of dust. The cross method may be used to determine the particle hardness. For example, if the sample does not break when scratched with a fingernail but breaks when scratched with a copper wire, the batch of samples is recorded as corresponding to a Mohs hardness of 2 to 3. Without wishing to be bound by any particular theory, the high hardness of the compositions of the present disclosure may be a physical manifestation of a high degree of crystallinity, and this may be the basis for their performance as adsorbents for DLE.

[0205] In one embodiment of the present disclosure, the LIAH composition may be robust to degradation for at least about 500 column cycles. In one embodiment of the present disclosure, the LIAH composition is robust to degradation for at least about 5000 column cycles.

[0206] Manufacturing H 2 -LIAH composition method

[0207] According to one embodiment of the present disclosure, H is prepared as follows 2-LIAH composition. Lithium chloride (0.961 kg) was dissolved in a solution of AlCl3 (21.733 kg, 25-30%) and mixed with an overhead stirrer so that the molar ratio of Li:Al was about 1:2. The mixing rate was set to about 240 rpm, and an aliquot of NaOH solution (2.18 kg, 50%) was mixed with an aliquot of the LiCl / AlCl3 mixture. The pH of the reaction mixture was monitored, and when it increased to greater than about 10, the temperature of the reaction mixture was increased to about 90°C to about 97°C. Mixing was continued, another aliquot of the LiCl / AlCl3 solution was slowly added, and when the pH dropped to less than about 3, the reaction mixture was observed to thicken. When all the LiCl / AlCl3 solution was added, a gel-like material was formed. The mixing rate was reduced to about 100 rpm to reduce the possibility of excessive shearing of the material, and another aliquot of 50% NaOH solution was added until the pH of the gel-like material was about 6.8 to 7.2. The reaction mixture is weighed, transferred to a drying tray, and placed in a drying oven to age at about 95° C. for about 5 hours. The slurry is layered to less than about 4 cm to reduce the generation of fine particles (e.g., particles with a particle size of less than about 250 μm) and maintain a particle size range of about 250 μm to greater than about 2000 μm. After this period of time, the solid forms a wet cake, which is remixed and then dried to reduce its mass to 60% of its initial value. After cooling, the solid is desalted (e.g., NaCl is removed) by rinsing with deionized water under suction until the rinse solution reaches a conductivity of less than about 15 ms / cm. The final gel is transferred back to the oven and dried at about 95° C. for about 16 hours to about 24 hours to obtain H 2 -LIAH composition of the dry product. 2 The LIAH composition is sieved to obtain a particle fraction having a particle size ranging from about 250 μm to greater than about 2000 μm, and the H 2 -LIAH compositions were characterized.

[0208] According to one embodiment of the present disclosure, H is prepared as follows 2-LIAH composition. Lithium chloride (0.961 kg) was mixed with AlCl3 solution (17.045 kg, 28-30%) so that the molar ratio of Li:Al was about 1:2, respectively. The LiCl / AlCl3 mixture was mixed at 200 rpm to ensure complete dissolution of the salt. NaOH pellets (110 g) were dissolved separately in deionized water (380 mL) to form a 7.2 M (or approximately 29% wt / vol) hydroxide solution. The LiCl / AlCl3 mixture was slowly added (at a rate of 2 L / min) to the hydroxide solution while mixing with an overhead mixer and monitoring the pH of the reaction mixture. Before the addition of the LiCl / AlCl3 mixture was completed, the pH of the reaction mixture decreased from greater than about 12 to less than about 3. During the process of the reaction mixture approaching the minimum value of this pH transition, the solution viscosity increased significantly, and the mixing rate was increased to be sufficient to maintain a vortex in the gel-like material while avoiding potential excessive shear. After the addition of the LiCl / AlCl3 mixture, mixing was continued for about 10 minutes. Then, the mixing rate was reduced to 100 rpm, and another aliquot of the hydroxide solution was added to adjust the pH of the gel-like material to about 7.0. The gel-like material remained unchanged, and the viscosity of the reaction mixture was not significantly reduced. The reaction mixture was transferred to a set of drying trays and weighed, each tray was loaded to a minimum thickness of about 4 cm to reduce the excessive production of fine particles (e.g., <250 μm) and to maintain a particle size range of about 250 μm to greater than about 2000 μm. The loaded drying trays were placed in a drying oven, where the reaction mixture was aged at about 95° C. for 5 hours. After this period of time, the solid formed a wet cake, which was remixed and then continued to dry to reduce its mass to about 70% of its initial value. After cooling, the solid was desalted (to remove NaCl) by rinsing with deionized water under suction filtration until the rinse solution reached a conductivity of less than about 15 ms / cm. The final gel-like material was transferred back into the oven and dried at 95° C. for 24 hours to obtain H 2 -LIAH composition of the dry product. 2 The LIAH composition is sieved to obtain a particle fraction having a particle size ranging from about 250 μm to greater than about 2000 μm, and the H 2 -LIAH compositions were characterized.

[0209] In one embodiment of the present disclosure, as the reaction mixture approaches the minimum of the pH transition associated with the addition of the LiCl / AlCl3 mixture and the gel-like material forms, the mixing time can be selected to balance the following: (i) improving homogeneity, thereby adjusting the strength of the gel; (ii) reducing the formation of carbonates produced by long-term exposure to the atmosphere; and / or (iii) reducing the formation of impurities.

[0210] One aspect of the present disclosure relates to a method of making a LIAH composition, the method comprising:

[0211] (i) combining an initial aliquot of a hydroxide solution with an initial aliquot of a solution comprising a lithium halide and an aluminum halide to form a reaction mixture, wherein the hydroxide solution is in excess such that the pH of the reaction mixture is at least about 9.0;

[0212] (ii) adding an additional aliquot of a solution comprising a lithium halide and an aluminum halide to the reaction mixture such that the pH of the reaction mixture is reduced to less than about 4.0;

[0213] (iii) allowing the reaction mixture to form a gel-like material; and

[0214] (iv) adding an additional aliquot of the hydroxide solution to the reaction mixture to raise the pH of the reaction mixture to about 6.5 to about 7.5.

[0215] In one embodiment of the present disclosure, in step (i), an initial aliquot of the hydroxide solution is added to an initial aliquot of the solution comprising lithium halide and aluminum halide.

[0216] In one embodiment of the present disclosure, in step (i), an initial aliquot of a solution comprising lithium halide and aluminum halide is added to an initial aliquot of a hydroxide solution.

[0217] In one embodiment of the present disclosure, the initial aliquot of the solution comprising lithium halide and aluminum halide and the additional aliquots of the solution comprising lithium halide and aluminum halide are derived from the same stock solution.

[0218] In one embodiment of the present disclosure, the initial aliquot of the hydroxide solution and the additional aliquots of the hydroxide solution are derived from the same stock solution.

[0219] In one embodiment of the present disclosure, the solution comprising lithium halide and aluminum halide has a lithium:aluminum molar ratio of about 1.0:2.0 to about 1.0:3.0.

[0220] In one embodiment of the present disclosure, the concentration of the hydroxide solution is about 6.5M to about 8.0M.

[0221] In one embodiment of the present disclosure, the lithium halide is lithium fluoride, lithium chloride, lithium bromide, lithium iodide or a combination thereof.

[0222] In one embodiment of the present disclosure, the lithium halide is lithium chloride.

[0223] In one embodiment of the present disclosure, the aluminum halide is aluminum trifluoride, aluminum trichloride, aluminum tribromide, aluminum triiodide, or a combination thereof.

[0224] In one embodiment of the present disclosure, the aluminum halide is aluminum trichloride.

[0225] In one embodiment of the present disclosure, the hydroxide solution is a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, a magnesium hydroxide solution, or a combination thereof.

[0226] In one embodiment of the present disclosure, the hydroxide solution is a sodium hydroxide solution.

[0227] In one embodiment of the present disclosure, the addition rate of the hydroxide solution is about 9.5 mL / min to about 10.5 mL / min.

[0228] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the reaction mixture is stirred to adjust the viscosity of the gel-like material.

[0229] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the temperature of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

[0230] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the pressure of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

[0231] In one embodiment of the present disclosure, in step (iii), step (iv) or a combination thereof, the reaction time is controlled to adjust the viscosity of the gel-like material.

[0232] In one embodiment of the present disclosure, in step (ii), step (iv) or a combination thereof, the rate of addition is controlled to adjust the viscosity of the gel-like material.

[0233] In one embodiment of the present disclosure, the method further comprises: (v) solidifying the gel-like material into a LIAH composition.

[0234] In one embodiment of the present disclosure, step (v) comprises drying at a temperature of about 85°C to about 95°C.

[0235] In one embodiment of the present disclosure, step (v) comprises drying for about 24 hours to about 75 hours.

[0236] In one embodiment of the present disclosure, drying is included at a pressure of about 76 mmHg to about 760 mmHg.

[0237] In one embodiment of the present disclosure, step (v) comprises aging, rinsing, drying, sieving or a combination thereof.

[0238] One aspect of the present disclosure relates to a sorbent produced by a method as defined herein.

[0239] Mixing rate, increasing reactant concentrations, order of reagent addition relative to stoichiometric control, and viscosity changes correspond to increases in gel strength.

[0240] The increase in gel strength is associated with a higher amount of crystalline hydrates.

[0241] In contrast to the above schemes utilizing a pH reversal scheme, conventional LIAH manufacturing methods employ the following steps: (i) adding a LiCl / AlCl3 solution to a hydroxide solution without significantly decreasing the pH below about 6.5; or (ii) not controlling the pH during the addition of a stoichiometric amount of LiCl / AlCl3 solution to a hydroxide solution such that the final pH of the mixture is greater than 6.5, thereby not producing a gel-like material and not forming the H described herein. 2 -LIAH composition.

[0242] For use H 2 - Apparatus and method for recovering lithium from brine using LIAH composition

[0243] Figure 8 An apparatus 800 for recovering lithium from a lithium-containing solution according to one embodiment of the present disclosure is shown. Figure 8 Also shown is a method 850 for recovering lithium from a lithium-containing solution according to one embodiment of the present disclosure. Apparatus 800 is configured to perform method 850 using a guide column, guard, elution column configuration. The guide column is represented by cross-hatching, the guard column is represented by horizontal hatching, and the elution column is represented by vertical hatching. During operation, these columns are rotated throughout the extraction cycle. Figure 8 The process is depicted in , where apparatus 800 includes columns 808, 810, and 812 that process brine according to steps 852, 854, and 856 as follows.

[0244] In step 852, column 808 absorbs lithium, while column 810 acts as a guard column to collect any remaining lithium before the depleted brine is discharged as a raffinate, which can be recycled for further lithium extraction, further processing, storage or disposal. In addition, in step 802, the eluate is passed through column 812 to desorb the lithium absorbed in the previous cycle. This provides a lithium enhanced eluate that can be sent to a water recovery technology.

[0245] In step 854, column 810 is reconfigured from a guard column to a guide column. Column 810 receives brine and absorbs lithium therefrom. Also, in step 854, column 812 is reconfigured from an elution column to a guard column, and it absorbs the remaining lithium. Also, in step 854, column 808 is reconfigured from a guide column to an elution column, and it desorbs the lithium retained from step 852.

[0246] In step 856, column 812 is reconfigured from a guard column to a guide column. Column 812 receives brine and absorbs lithium therefrom. Also, in step 856, column 808 is reconfigured from an elution column to a guard column, and it absorbs the remaining lithium. Also, in step 856, column 810 is reconfigured from a guide column to an elution column, and it desorbs the lithium retained from step 854.

[0247] Steps 852, 854, and 856 may be performed cyclically by adjusting a valve manifold (or alternative means for fluid control) to direct the flow of brine, eluent, etc.

[0248] As those skilled in the art will appreciate, apparatus 800 is one of many configurations that may be suitable for recovering lithium in the context of the present disclosure (and also for method 850), as apparatus and methods for recovering lithium from lithium-containing solutions are generally known to those skilled in the art. PCT Patent Publication: WO WO2020 / 257937A1 (the contents of which are incorporated herein by reference) may disclose apparatus and methods for recovering lithium from brine, which are suitable for use in the context of the present disclosure. Those skilled in the art should understand the scientific and engineering basis (e.g., equilibrium and mass transfer factors) associated with the use of adsorbents in such apparatus and / or methods, as evidenced by Gableman, A., "Absorption Basics: Part 1," Chemical Engineering Progress, 113(7), pp48-53 (July 2017), the contents of which are incorporated herein by reference. For example, the apparatus for lithium recovery according to the present disclosure can be configured as a sequential flow system (also referred to as a "daisy chain" flow system), which is configured to flow in an upward flow or downward flow mode in parallel, series, or a combination of series and parallel. Similarly, the apparatus for lithium recovery according to the present disclosure can adopt countercurrent extraction. In countercurrent extraction, the eluent is pumped countercurrently to the direction of the adsorbent forward, for example by indexing a multi-port valve system and / or a turntable composed of an adsorbent container. The apparatus for lithium recovery according to the present disclosure can be configured to operate under various temperature and pressure conditions. For example, the apparatus for lithium recovery according to the present disclosure can operate at a temperature below about 60°C, about 60°C to about 100°C, and / or above about 100°C.

[0249] In the context of the present disclosure, the lithium-containing solution can be a brine, such as a brine recovered from a naturally occurring terrestrial brine mine. The lithium-containing solution can also be a fluid brine suspension produced from hydraulic mining operations in geological formations and / or brines and wastewaters produced from oil and gas production activities. The composition of the lithium-containing solution suitable for the adsorbent, apparatus and / or method of the present disclosure can vary greatly. For example, a lithium-containing solution having a total dissolved solids (TDS) of about 50 ppm to about 5000 ppm, about 5000 ppm to about 10000 ppm, about 10000 ppm to about 100000 ppm or about 100000 to about 250000 ppm may be suitable. In terms of cation loading, a suitable lithium-containing solution may contain different concentrations of lithium, sodium, potassium, calcium, magnesium or a combination thereof. For example, a lithium-containing solution may contain about 5000 ppm of K + , about 1000ppm Na + , about 500ppm Li + and about 50ppm Ca2 + .

[0250] In the context of the present disclosure, the term "brine" may refer to natural brine, synthetic brine, or a combination thereof. In the context of the present disclosure, the term "ion" is defined as a metal ion of any valence, including but not limited to lithium, potassium, calcium, magnesium, manganese, iron, zinc, cobalt, nickel, titanium, aluminum, tin, gallium, silver, gold, copper, cadmium, or a combination thereof. In the context of the present disclosure, the term "lithium" is broadly used to cover lithium ions in solution, lithium ions adsorbed to a surface, and lithium ions in chemical compositions such as lithium chloride, lithium carbonate, and lithium hydroxide. It will be appreciated by those skilled in the art that lithium ions can take a variety of forms, all of which are within the scope of the present disclosure. For example, lithium ions can be hydrated, participate in coordinated ion pairs, be retained in interstitial positions, and be suspended in colloidal form, etc.

[0251] One aspect of the present disclosure relates to an apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising: a container having an inlet, an outlet, and a continuous flow path therebetween; and an adsorbent comprising H2O2 having a molar ratio of crystalline hydrate to lithium of at least 2.1:1.0. 2 -LIAH composition.

[0252] One aspect of the present disclosure relates to an apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising: a vessel having an inlet, an outlet and a continuous flow path therebetween; and a sorbent as defined herein.

[0253] One aspect of the present disclosure relates to a method for recovering lithium from a lithium-containing solution, the method comprising: contacting the lithium-containing solution with an adsorbent composition to extract lithium from the lithium-containing solution; and eluting lithium from the adsorbent composition to form a lithium elute solution, wherein the adsorbent composition comprises a LIAH composition having a molar ratio of crystalline hydrate:lithium of at least 2.1:1.0.

[0254] One aspect of the present disclosure relates to a method for recovering lithium from a lithium-containing solution, the method comprising: contacting the lithium-containing solution with an adsorbent composition to extract lithium from the lithium-containing solution; and eluting lithium from the adsorbent composition to form a lithium wash solution, wherein the adsorbent composition comprises a LIAH composition as defined herein.

[0255] One aspect of the present disclosure relates to a method for recovering lithium from a lithium-bearing solution, the method comprising: contacting the lithium-bearing solution with an adsorbent comprising a LIAH composition as defined herein to extract lithium from the lithium-bearing solution; and eluting lithium from the adsorbent to form a lithium wash solution.

[0256] Additional Notes

[0257] Although the present disclosure has been described and illustrated with respect to preferred embodiments and preferred applications thereof, the present disclosure is not limited thereto since modifications and variations are possible in the present disclosure as will be appreciated by those skilled in the art and which are within the full intended scope of the present disclosure.

[0258] While particular aspects of the subject matter described herein have been shown and described, it will be apparent to those skilled in the art that changes and modifications may be made based on the teachings herein without departing from the subject matter described herein and its broader aspects, and the appended claims are intended to cover within their scope all such changes and modifications as are within the true spirit and scope of the subject matter described herein.

[0259] Note that in this specification and the drawings, the same features of the invention may be represented by more than one reference numeral. Figure 1 The feature indicated by reference numeral 100 is Figure 2 In the Figure 3 In the drawings, the features indicated by the same reference numerals are equivalent and / or identical features in different embodiments and should be considered equivalent and / or identical for the purpose of interpreting this specification and / or drawings.

[0260] It should be understood by those skilled in the art that, in general, the terms used herein (especially those used in the appended claims) are generally intended to be “open” terms (for example, the term “comprising” should be interpreted as “including but not limited to,” the term “having” should be interpreted as “having at least,” the term “has” should be interpreted as “has at least,” etc.).

[0261] It will also be understood by those skilled in the art that if a particular number of an introduced claim statement is intended, such intent will be expressly stated in the claim, and in the absence of such a statement, such intent is absent. For example, to aid understanding, the following appended claims may include the use of the introductory phrases "at least one" and "one or more" to introduce claim statements. However, the use of these phrases should not be interpreted as implying that a claim statement introduced by the indefinite article "a or an" limits any particular claim containing such introduced claim statement to claims containing only one such statement, even when the same claim includes the introductory phrases "one or more" or "at least one" and an indefinite article such as "a or an" (e.g., "a and / or an" should generally be interpreted as meaning "at least one" or "one or more"); the same applies to the use of definite articles used to introduce claim statements. In addition, even if a particular number of an introduced claim statement is explicitly enumerated, those skilled in the art will recognize that such enumeration should generally be interpreted as meaning at least the number enumerated (e.g., a simple enumeration of "two statements" without other modifiers generally means at least two statements or two or more statements).

[0262] Furthermore, in those cases where a convention similar to “at least one of A, B, and C, etc.” is employed, generally speaking, such construction is intended to enable one skilled in the art to understand the convention (e.g., “a system having at least one of A, B, and C” would include but is not limited to systems having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B and C, etc.). In those cases where a convention similar to “at least one of A, B, or C, etc.” is employed, generally speaking, such construction is intended to enable one skilled in the art to understand the convention (e.g., “a system having at least one of A, B, or C” would include but is not limited to systems having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B and C, etc.).

[0263] It should also be understood by those skilled in the art that disjunctive words and / or phrases generally indicating two or more alternative terms (whether in the specification, claims or drawings) should be understood to include the possibility of one, any or both terms, unless the context dictates otherwise. For example, the phrase "A or B" should generally be understood to include the possibility of "A" or "B" or "A and B".

[0264] With respect to the appended claims, it will be appreciated by those skilled in the art that the operations listed therein may generally be performed in any order. In addition, although the various operational flows are presented in one or more sequences, it will be appreciated that the various operations may be performed in other sequences different from the sequence shown, or may be performed simultaneously. Examples of these alternative sequences may include overlapping, interleaved, interrupted, reordered, incremental, preparatory, supplementary, parallel, reverse, or other different sequences, unless the context dictates otherwise.

[0265] Throughout this application, terms such as "in one embodiment," "in a certain embodiment," "in an embodiment," "in several embodiments," "in at least one embodiment," "in various embodiments," and the like may be used. Each of these terms and all similar terms should be interpreted as "in at least one embodiment, and possibly but not necessarily in all embodiments," unless expressly stated otherwise. Specifically, unless expressly stated otherwise, similar phrases are intended to provide non-exclusive and non-limiting examples of implementations of the subject matter.

[0266] The degree term "substantially" as used herein refers to a reasonable amount of deviation of the modified term so that the end result will not change significantly. The term "substantially" should be interpreted as including ±5% deviation of the modified term, provided that the deviation does not negate the meaning of the term it modifies. The degree terms "approximately" and "approximately" should be interpreted as including ±20% deviation. For example, when the term "approximately" or "approximately" is used in conjunction with a numerical value, these terms modify the value with a change of more or less than 20% compared to the nominal value. The term can also take into account, for example, experimental errors of measuring equipment or rounding. Other degree terms should be interpreted as including ±5% deviation of the modified term.

[0267] When a numerical range is mentioned herein, the lower and upper limits of the range are always included in the definition unless otherwise stated. When a numerical range is mentioned herein, all intermediate ranges and subranges as well as individual values ​​contained in these ranges are intended to be included.

[0268] Simply stating that one, some or possible embodiments include one or more things or have one or more features does not mean that all embodiments include one or more things or have one or more features, nor does it imply that these embodiments must exist. It only illustrates an example and should not be interpreted in other ways unless explicitly stated.

[0269] Those skilled in the art will appreciate that the specific exemplary compositions, devices and / or methods described above are representative of more general processes and / or apparatus and / or techniques taught elsewhere herein, such as in the appended claims and / or elsewhere in the present disclosure.

Claims

1. An adsorbent for recovering lithium from a lithium-containing solution, the adsorbent comprising highly hydrated lithium-bound aluminum hydroxide (H 2 -LIAH) composition having a crystalline hydrate:lithium ratio of at least about 2.1:1.

0.

2. The adsorbent according to claim 1, wherein the H 2 The LIAH composition has a crystalline hydrate:lithium ratio of about 2.1:1.0 to about 4.3:1.

0.

3. The adsorbent according to claim 1 or 2, wherein the H 2 The LIAH composition has a crystalline hydrate:lithium ratio of 2.1:1.0 to about 2.9:1.

0.

4. The adsorbent according to claim 1 or 2, wherein the H 2 The LIAH composition has a crystalline hydrate:lithium ratio of 2.9:1.0 to about 4.0:1.

0.

5. The adsorbent according to any one of claims 1 to 4, wherein the H 2 The crystalline hydrate:lithium ratio of the LIAH composition is determined by differential scanning calorimetry, inductively coupled plasma optical emission spectroscopy, thermogravimetric analysis, or a combination thereof.

6. The adsorbent according to any one of claims 1 to 5, wherein the H 2 The X-ray diffraction pattern of the LIAH composition has 2θ reflection peaks at 11.5° 2θ, 23.1° 2θ, 35.0° 2θ, 35.7° 2θ, or a combination thereof.

7. The adsorbent according to any one of claims 1 to 6, wherein the H 2 - The LIAH composition has an aluminum:lithium ratio of at least about 1.9:1.

0.

8. The adsorbent according to claim 7, wherein the H 2 - The LIAH composition has an aluminum:lithium ratio of about 2.0:1.0 to about 3.0:1.

0.

9. The adsorbent according to claim 8, wherein the H 2 - The LIAH composition has an aluminum:lithium ratio of about 2.4:1.0 to about 2.6:1.

0.

10. The adsorbent according to any one of claims 1 to 9, wherein the H 2 -LIAH composition is as described in Formula 1: Li a X·mAl(OH)3·nH2O cr Formula 1 in: In formula 1: a is about 1; X is a monovalent anion; m is from about 1.9 to about 3.0; n is from about 2.4 to about 4.3; and H2O cr Represents a crystalline hydrate.

11. The adsorbent according to any one of claims 1 to 10, wherein the H 2 -LIAH composition is a lithium aluminum layered double hydroxide composition.

12. The adsorbent according to any one of claims 1 to 11, further comprising a binder, a coating agent or a combination thereof.

13. The adsorbent according to any one of claims 1 to 12, wherein the H 2 - The LIAH composition has a lithium uptake capacity of at least about 8.0 mg / mL.

14. The adsorbent according to claim 13, wherein the H 2 - The LIAH composition has a lithium uptake capacity of at least about 9.0 mg / mL.

15. The adsorbent according to claim 14, wherein the H 2 - The lithium uptake capacity of the LIAH composition is from about 9.5 mg / mL to about 12.0 mg / mL.

16. The adsorbent according to any one of claims 1 to 15, wherein the H 2 - The LIAH composition can be processed to provide a particle size distribution in which at least about 40% of the particles are between about 500 μm and about 1000 μm.

17. The adsorbent according to any one of claims 1 to 15, wherein the H 2 - The LIAH composition can be processed to provide a particle size distribution in which at least about 50% of the particles are between about 500 μm and about 1000 μm.

18. The adsorbent according to any one of claims 1 to 15, wherein the H 2 - The LIAH composition can be processed to provide a particle size distribution in which at least about 55% of the particles are between about 500 μm and about 1000 μm.

19. The adsorbent according to any one of claims 1 to 18, wherein the H 2 The LIAH composition is suspended in deionized water to provide a solution having a pH of about 7.0 to about 6.

2.

20. The adsorbent according to any one of claims 1 to 19, wherein the H 2 - The LIAH composition was suspended in deionized water to provide a turbidity value of less than 10 NTU.

21. The adsorbent according to any one of claims 1 to 19, wherein the H 2 - The LIAH composition was suspended in deionized water to provide a turbidity value of less than 5 NTU.

22. The adsorbent according to any one of claims 1 to 19, wherein the H 2 The LIAH composition is suspended in deionized water to provide a turbidity value of about 2 NTU to about 5 NTU.

23. The adsorbent according to any one of claims 1 to 22, wherein the H 2 - The LIAH composition has a Mohs hardness of at least about 5.

0.

24. The adsorbent according to claim 23, wherein the H 2 - The LIAH composition has a Mohs hardness of at least about 6.

0.

25. The adsorbent according to claim 24, wherein the H 2 - The LIAH composition has a Mohs hardness of at least about 7.

0.

26. The adsorbent according to any one of claims 1 to 25, wherein the H 2 - The LIAH composition is physically durable for at least about 500 cycles under operating conditions.

27. The adsorbent according to any one of claims 1 to 26, wherein the H 2 - The LIAH composition is physically durable for at least about 5000 cycles under operating conditions.

28. The sorbent of any one of claims 1 to 27, wherein the lithium-bound aluminum hydroxide composition is chemically durable for at least about 500 cycles under operating conditions.

29. The sorbent of any one of claims 1 to 28, wherein the lithium-bound aluminum hydroxide composition is chemically durable for at least about 5000 cycles under operating conditions.

30. A method of making a lithium-bound aluminum hydroxide composition, the method comprising: (i) contacting an initial aliquot of a hydroxide solution with an initial aliquot of a solution comprising a lithium halide and an aluminum halide to form a reaction mixture, wherein the hydroxide solution is in excess and the pH of the reaction mixture is at least about 9.0; (ii) adding an additional aliquot of a solution comprising a lithium halide and an aluminum halide to the reaction mixture such that the pH of the reaction mixture decreases to less than about 4.0; (iii) allowing the reaction mixture to form a gel-like material; as well as (iv) adding an additional aliquot of the hydroxide solution to the reaction mixture to raise the pH of the reaction mixture to about 6.5 to about 7.

5.

31. A method according to claim 30, wherein in step (i) an initial aliquot of the hydroxide solution is added to an initial aliquot of the solution comprising lithium halide and aluminium halide.

32. The method of claim 30, wherein in step (i), an initial aliquot of the solution comprising lithium and aluminum halides is added to an initial aliquot of the hydroxide solution.

33. The method of any one of claims 30 to 32, wherein the initial aliquot of the solution comprising lithium and aluminium halides and the further aliquots of the solution comprising lithium and aluminium halides are derived from the same stock solution.

34. The method of any one of claims 30 to 33, wherein the initial aliquot of the hydroxide solution and the further aliquots of the hydroxide solution are derived from the same stock solution.

35. The method of any one of claims 30 to 34, wherein the solution comprising lithium halide and aluminum halide has an aluminum:lithium molar ratio of at least about 1.9:1.

0.

36. The method of any one of claims 30 to 35, wherein the concentration of the hydroxide solution is from about 6.5M to about 8.0M.

37. A method according to any one of claims 30 to 36, wherein the lithium halide is lithium chloride.

38. The method of any one of claims 30 to 37, wherein the aluminum halide is aluminum trichloride.

39. The method of any one of claims 30 to 38, wherein the hydroxide solution is a sodium hydroxide solution.

40. The method of any one of claims 30 to 39, wherein in step (ii), the rate of adding the hydroxide solution is from about 9.8 L / min to about 10.8 L / min.

41. The method of any one of claims 30 to 40, wherein in step (iii), step (iv) or a combination thereof, the reaction mixture is stirred to adjust the viscosity of the gel-like material.

42. The method of any one of claims 30 to 41, wherein in step (iii), step (iv) or a combination thereof, the temperature of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

43. The method according to any one of claims 30 to 42, wherein in step (iii), step (iv) or a combination thereof, the pressure of the reaction mixture is controlled to adjust the viscosity of the gel-like material.

44. The method according to any one of claims 30 to 42, wherein in step (iii), step (iv) or a combination thereof, the reaction time is controlled to adjust the viscosity of the gel-like material.

45. The method of any one of claims 30 to 44, wherein in step (ii), step (iv) or a combination thereof, the rate of addition is controlled to adjust the viscosity of the gel-like material.

46. ​​The method according to any one of claims 30 to 45, further comprising: (v) solidifying the gel-like material into H 2 -LIAH composition.

47. The method of claim 46, wherein step (v) comprises drying at a temperature of about 85°C to about 105°C.

48. The method of any one of claims 46 to 47, wherein step (v) comprises drying for about 24 hours to about 75 hours.

49. The method of any one of claims 46 to 48, wherein step (v) comprises drying at a pressure of about 76 mmHg to about 760 mmHg.

50. The method of any one of claims 46 to 49, wherein step (v) comprises rinsing, drying, sieving or a combination thereof.

51. A highly hydrated lithium-bound aluminium hydroxide composition produced by a process as defined in any one of claims 30 to 50.

52. An apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising: a container having an inlet, an outlet, and a flow path therebetween; as well as The adsorbent in the container comprises a highly hydrated lithium-bonded aluminum hydroxide composition having a crystalline hydrate:lithium molar ratio of about 2.1:1.0 to about 4.3:1.

0.

53. An apparatus for recovering lithium from a lithium-containing solution, the apparatus comprising: a container having an inlet, an outlet, and a flow path therebetween; as well as An adsorbent in the container, wherein the adsorbent is as defined in any one of claims 1 to 29.

54. A method for recovering lithium from a lithium-containing solution, the method comprising: contacting the lithium-containing solution with an adsorbent to extract lithium from the lithium-containing solution; as well as eluting lithium from the adsorbent to form a lithium elution solution, The adsorbent comprises a highly hydrated lithium-bonded aluminum hydroxide composition having a molar ratio of crystalline hydrate to lithium of about 2.1:1.0 to 4.3:1.

0.

55. A method for recovering lithium from a lithium-containing solution, the method comprising: contacting the lithium-containing solution with an adsorbent as defined in any one of claims 1 to 29 to extract lithium from the lithium-containing solution; as well as Lithium is eluted from the adsorbent to form a lithium elution solution.

Citation Information

Patent Citations

  • System and method for processing and concentrating selected IONS in brine solutions

    WO2020257937A1